Outcomes of urgent/emergent transcatheter mitral valve repair (MitraClip): A single center experience. Issue 3 (26th June 2020) - Kovach, Christopher P.; Bell, Sean; Kataruka, Akash; Reisman, Mark; Don, Creighton
Abstract: Objectives: To describe the outcomes of urgent/emergent transcatheter edge‐to‐edge mitral valve repair (TMVr) and compare the clinical, echocardiographic, and procedural characteristics of survivors and nonsurvivors. Background: TMVr is a treatment strategy for select patients with severe primary or secondary mitral regurgitation. However, knowledge regarding outcomes for urgent/emergent TMVr is limited. Methods: All urgent or emergent TMVr procedures using MitraClip performed at the University of Washington Medical Center between January 2018 and March 2019 were identified and clinical, echocardiographic, hemodynamic, procedural, and outcomes data were obtained by chart review. Outcomes included all‐cause mortality, hospital mortality, procedural success, periprocedural complications, and hospital readmission. Results: Of the 20 patients who underwent urgent/emergent TMVr, eight were treated for cardiogenic shock (CS), four for acute decompensated heart failure (ADHF) with hypoxemic respiratory failure requiring mechanical ventilation, and eight for ADHF with failure of inpatient medical therapy. Mechanical circulatory support (MCS) was used in six patients; preceding TMVr in three patients and immediately post‐TMVr in three patients. Overall, 30‐day mortality and hospital readmission rates were 21 and 13%, respectively. Over a median 153 days (IQR 20–491) of follow‐up, 10 patients (50%) died. Preprocedure CS, new or ongoing MCS post‐TMVr, refractory respiratory failure post‐TMVr, and acute kidney injury post‐TMVr were associated with mortality. Conclusions: In a single‐center retrospective analysis, urgent/emergent TMVr in high‐risk patients with ADHF or CS was associated with high short‐term mortality and periprocedural complications. Prospective studies are warranted to inform patient selection and periprocedural management for urgent/emergent TMVr.